2022
DOI: 10.1002/fsn3.2772
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and production of persimmon milk drink and evaluation of its physicochemical, rheological, and sensorial properties

Abstract: One of the effective ways for increasing milk intake in a diet is producing flavored milk. In the present study, flavored persimmon milk drinks were formulated and produced. Rheological, sensorial, and physicochemical properties of the drinks were evaluated. Different amounts of persimmon (5, 10, 20, and 30% W/V), gum Arabic (0.1 and 0.2% W/V), and sugar (3 and 5% W/V) were used to produce persimmon milk. All the experiments were done in a completely randomized design (CRD) in three replicates. First, persimmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
(77 reference statements)
1
0
0
Order By: Relevance
“…Statistical analysis of sensory evaluation of overall acceptability showed that, there was significant change (p≤0.05) among samples. These are agreed with Jokar and Azizi (2022) who found that fortification of YD with PF enhancement the Sensory attributes of YD.…”
Section: Sensory Evaluation Of Yoghurt Drink Supplemented With Persim...supporting
confidence: 91%
“…Statistical analysis of sensory evaluation of overall acceptability showed that, there was significant change (p≤0.05) among samples. These are agreed with Jokar and Azizi (2022) who found that fortification of YD with PF enhancement the Sensory attributes of YD.…”
Section: Sensory Evaluation Of Yoghurt Drink Supplemented With Persim...supporting
confidence: 91%
“…Jokar and Azizi [35] reported yield stress increment of 1.43-7.12 pa with an increase of persimmon juice content from 10% to 20%. Additionally, Silva et al [34] also reported Herschel Bulkley character of plant-based beverages with a flow index ranging from 0.710 to 0.825. Similar behavior was also reported by Lopes et al [36] for ultra-high temperature (UHT) nut beverages.…”
Section: Stress-strain Relationship Of Beveragesmentioning
confidence: 96%
“…The power law modeling of the shear stress and shear rate parameters of the beverages are shown in Table 2. The flow index (n) of unity (n = 1), n < 1.0, and n > 1.0 indicates Newtonian character, pseudoplastic and dilatant behavior respectively [34]. The flow index (n) of the beverage samples ranged from 0.1948 to 0.8214, and the yield stress required to initiate flow ranged from 0.013 Pa to 0.037 Pa, hence the beverage samples showed pseudoplastic behavior with Herschel Bulkley character.…”
Section: Stress-strain Relationship Of Beveragesmentioning
confidence: 99%
“…Flavored milk is a delectable and nutrient-rich beverage choice, and its production is one of the most effective ways to increase milk intake in a diet [1,2]. It has been recommended as a beverage option by the American Heart Association and the American Academy of Pediatrics because it may increase the nutrient intake of calcium, vitamin D, and potassium [3,4].…”
Section: Introductionmentioning
confidence: 99%